Research Trend of Environmental Education in Science Based on Scopus Database - Putih Sari; Tarzan Purnomo; Eko Hariyono (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2023)
Objective: This study analyzes the trend of implementing environmental education in science research. Method: This research was conducted using the bibliometric literature study method. The data collection of this study used a Scopus database and was analyzed by the Vosviewer application. Result: From this study known that there is a significant increase in environmental education science research. The highest number of publications carried out in 2021 was six articles. The results of the VOSviewer visualization found 3 clusters red, green, and blue. Red cluster show related keyword research about education, curriculum, learning science, and education program. Green cluster show related keyword research about environmental education and science education. Blue cluster show related keyword research about sustainable development, science and technology, environmental technology, environmental science, and environmental sustainability. From the cluster, there are known that some theme related can be used to combine and use to research environmental education in science. Novelty: Analysis of these research trends can be used as a reference and a means of developing self-abilities concerning being an environmental educator in schools. Implementing environmental education can make students better understand and explore their abilities in science.